The Lockdown Impact on the Relations between Portuguese Parents and Their 1- to 3-Year-Old Children during the COVID-19 Pandemic - Vian, F (2022)
Many countries have applied mandatory confinement measures in response to the COVID-19 pandemic, such as school and kindergarten closures, which confined families to their homes. The study concerns the impacts of the first COVID-19 lockdown on the relationships between Portuguese parents and their children, in a non-clinical population composed of fathers and mothers of children between the ages of 12 months and 3 years and 364 days. An online questionnaire (set by the research team) and the Parenting Daily Hassles Scale (PDHS) concerning the confinement period were applied between 17 June and 29 July 2020. To assess the impacts of the lockdown, outcomes regarding the impacts perceived by the parents, the potential regression in the development of children, and the willingness to promote changes in family routines in the future, were considered. Of the total sample (n = 1885), 95.4% of the parents (n = 1798) said that, after confinement, the relationship with their children had improved or remained similar to the pre-confinement period; 97.3% (n = 1835) noticed positive changes in the development of their children, and 63.7% (n = 1200) noted that the relationships with their children during the confinement period would lead to some changes in family routines in the future. Multivariate regression analyses showed that most of the sociodemographic variables chosen were not associated with the outcomes. However, significant levels of pressure over parenting and parental overload (reported by high scores in the PDHS intensity and frequency scales), challenging behaviors of the children, and the impacts they had on parental tasks had negative influences on the studied outcomes. On the contrary, the number of adults living with their children, the perceptions regarding the development of their children, and sharing new experiences with them were significant factors for positively-perceived impacts on the relationships between them or in the desire to bring about changes in family routines in the future. The impacts of the lockdown on the relationships between parents and children aged between 1 and 3 years old were more dependent on relational aspects and on the parents' sense of competence in exercising parental functions. We conclude that, despite the increased demands imposed by the lockdown, nearly all of the parents evaluated the quality of the relationship with their children as positive after this period.